2016
DOI: 10.1371/journal.pcbi.1005245
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Heterogeneity Generates Re-entrant Substrate during Atrial Fibrillation and Anti-arrhythmic Drug Action: Mechanistic Insights from Canine Atrial Models

Abstract: Anti-arrhythmic drug therapy is a frontline treatment for atrial fibrillation (AF), but its success rates are highly variable. This is due to incomplete understanding of the mechanisms of action of specific drugs on the atrial substrate at different stages of AF progression. We aimed to elucidate the role of cellular, tissue and organ level atrial heterogeneities in the generation of a re-entrant substrate during AF progression, and their modulation by the acute action of selected anti-arrhythmic drugs. To exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 47 publications
7
57
0
Order By: Relevance
“…In contrast, when the grid contained 2 APD regions with a soft boundary between the 2, extrastimuli caused sustained rotors with the singularity point fixed at the boundary between the 2 APD regions ( Figure 5M, Supplemental Video 3). Thus, similar to previously published modeling studies (11,23,24), we found that heterogeneity of the APD is sufficient to form a suitable substrate to perpetuate AF.…”
Section: Resultssupporting
confidence: 90%
“…In contrast, when the grid contained 2 APD regions with a soft boundary between the 2, extrastimuli caused sustained rotors with the singularity point fixed at the boundary between the 2 APD regions ( Figure 5M, Supplemental Video 3). Thus, similar to previously published modeling studies (11,23,24), we found that heterogeneity of the APD is sufficient to form a suitable substrate to perpetuate AF.…”
Section: Resultssupporting
confidence: 90%
“…Our study provides insights into the conditions for the emergence of such triggers, as well as cellular models that can be integrated into 3D atrial models to simulate such triggers. Currently, even highly detailed 3D atrial models [11,12] rely on fast pacing for the initiating of AF, and the introduction of a natural triggering mechanism will prove valuable in furthering the understanding of the complex mechanisms underlying AF. and SERCA activity is enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Models of the human atrial action potential are a subject of research interest and clinical relevance because heterogeneity in action potential shape and duration in different parts of the atria is associated with vulnerability to atrial fibrillation (Varela et al, 2016), and persistence of atrial fibrillation is associated with remodeling of the atrial action potential Colman et al, 2013). There are several different models of human atrial myocytes, each with different properties Wilhelms et al, 2012).…”
Section: Human Atrial Cell Modelsmentioning
confidence: 99%